2016
DOI: 10.3109/08820538.2015.1114865
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Nanoparticles: Toxicity Comparison in Retinal Pigment Epithelium and Retinal Vascular Endothelial Cells

Abstract: Multiple synthetic polymer nanoparticles (NPs) have been widely used as drug delivery systems. However, their toxicity to the retinal pigment epithelium and retinal endothelium remains unclear. In this study, we analyze the cytotoxic effects of three different kinds of NPs, made of poly lactic-co-glycolic acid (PLGA), polycaprolactone (PCL), and PEGylated PLGA (PEG-PLGA), in a retinal pigment epithelium cell line (ARPE-19) and in primary human retinal vascular endothelial cells (RVEC). PEG-PLGA NPs presented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…These high concentrations of formulation excipients might have contributed to the slight decrease in the cell viability at higher studied concentrations. The concentration-dependent increase in cytotoxicity of PEG-PLGA polymer has been demonstrated in previous studies, even at concentrations below 200 µg/mL [ 36 ]. Further, it has been demonstrated that even the shape of nanoparticles formed with PEG-PLGA polymer influences their cytotoxicity, and shows cytotoxicity even below a concentration of 100 µg/mL [ 37 ].…”
Section: Resultsmentioning
confidence: 69%
“…These high concentrations of formulation excipients might have contributed to the slight decrease in the cell viability at higher studied concentrations. The concentration-dependent increase in cytotoxicity of PEG-PLGA polymer has been demonstrated in previous studies, even at concentrations below 200 µg/mL [ 36 ]. Further, it has been demonstrated that even the shape of nanoparticles formed with PEG-PLGA polymer influences their cytotoxicity, and shows cytotoxicity even below a concentration of 100 µg/mL [ 37 ].…”
Section: Resultsmentioning
confidence: 69%
“…Hence, variations in surface characteristics, composition and size of the NPs and the various cell types used are likely to account for differences between the studies. This is corroborated by comparisons of the effects of different types of NPs on the cell viability of different cell types [28,32].…”
Section: Discussionmentioning
confidence: 77%
“…PEG- b -PCL-NPs were highly biocompatible and did not cause significant cell viability reductions when added to hCMEC/D3 cells at concentrations of [0.01–1 mg/mL] [27]. PCL-NPs resulted in different cytotoxicity in human retinal vascular ECs, exhibiting stronger effects in the latter at concentrations of [25 µg/mL] to [200 µg/mL] with up to 50% reduction in cell viability [28], indicating that different cell types react differently to similar NPs. In line with our findings, 20 nm PEGylated Au-NPs did affect the proliferation of HUVECs up to concentrations of [100 µg/mL], a lower Au-NP concentration than the one used in our study ([160.3 µg/mL]) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to avoid any hazards associated with systemic exposure, local application of CN03 to the eye is also a viable option. Besides the delivery as liposomal formulation it may be possible to combine CN03 with alternative drug delivery systems, such as poly(lactic- co -glycolic acid) for intraocular slow release ( 52 ) or cyclodextrins for topical delivery ( 53 ). Furthermore, the marked prolongation of its in vivo half-life with liposomal encapsulation, and the lack of therapeutic effect without, are in line with previous observations ( 19 , 39 ) and our findings thus stress the importance of efficient drug delivery for the treatment of retinal diseases.…”
Section: Discussionmentioning
confidence: 99%